Contribution of Internal Control Systems on Local Government Authorities Performance in Developing Countries - Chindengwike, James Daniel (Acta Universitatis Danubius. Œconomica, 2025)
The Controller and Auditor General’s reports, numerous companies face financial losses due to the poor internal control systems. This puts into doubt the effectiveness of the different internal control measures employed by several businesses. As a result, the purpose of this study is to assess the connection between internal control system and performance in Tanzanian Local Government Authorities (LGAs). The study used a descriptive research approach. This technique was acceptable since it examined and explained the relationship between variables in their natural condition without modifying them. The research involved 130 staff members from the Iramba Council, Singida District Council, and Manyoni District Council. The researcher selected the sample using simple random and selective sampling techniques. SPSS was used. Correlation and regression analysis were used to show the relationship between variables. Statistics were given as figures and tables. According to the paper, local governments may enhance their performance by including internal control systems such as risk assessment, monitoring, control actions, information and communication systems, and control environments. The results show a statistically significant relationship between control activities, risk assessment, information and communication, and performance in LGAs. Furthermore, the study discovered no statistically significant link between the monitoring and control environment and the performance of LGAs. The study focuses on internal control system such as risk assessment, monitoring, control actions, information and communication, and control environments. The study recommends that management commit to assisting all employees in developing effective internal control systems through interaction and training, allowing them to be guided on issues related to the proper implementation of accounting policies and procedures, thereby improving their professional skills and expertise. It is necessary to take legal action against individuals who abuse local government funds, and recovery must be achieved.